RESULTS OF POLYMORPHISM STUDIES OF POPULATION OF WHITE HEAD CABBAGE CV. AMAGER 611 - E. G. Dobrutskaya; E. G. Baranova; V. I. Orlova; V. I. Startsev; L. L. Bondareva (Овощи России)
The results of complex estimation of structure of variety population Amager 611, the genetic analysis by inbreeding (J1-J9) and RAPD-markers are shown. The role of 17 phenotype groups in the variety population was determined. The suggestions for agriculture and maintaining of cv. Amager 611 are proposed.